CA ALGINATE-MAGNETITE-RICE HUSK ASH BIOCOMPOSITE AS ADSORBENT TO REMOVE METHYLENE BLUE DYES - Ayuningsih, Citra
One of the synthetic dyes that is widely used is methylene blue (MB). The presence of MB in high doses in water can cause various problems because of its toxicity to animals, humans, and the environment. In this study, the composite adsorbent was developed from Ca Alginate- Magnetite-Rice Husk Ash (CA-Fe3O4-RHA) to remove MB. There are three stages carried out, namely adsorbent synthesis, adsorbent characterization, and adsorption studies. The adsorption study was carried out using a batch system to determine the optimum parameters of pH, contact time, adsorbent mass, and initial MB concentration. The results obtained the optimum conditions, namely pH 4, contact time 240 minutes, adsorbent mass 0,05 grams, and the initial concentration of MB 50 ppm. The uptake of MB by CA-Fe3O4-RHA biocomposite was obtained following the pseudo second order adsorption kinetics model and the Sips adsorption isotherm model.